2020
DOI: 10.1186/s41181-020-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and validation of [18F]mBPET-1, a fluorine-18 labelled mTOR inhibitor derivative based on a benzofuran backbone

Abstract: Background: Targeted therapy of HER2 positive breast cancer has led to clinical success in some cases with primary and secondary resistance being major obstacles. Due to the substantial involvement of mTOR kinase in cell growth and proliferation pathways it is now targeted in combination treatments to counteract HER2 targeted therapy resistance. However, the selection of receptive patient populations for a specific drug combination is crucial. This work aims to develop a molecular probe capable of identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As its name suggests, the CuAAC reaction is predicated on the Cu­(I)-catalyzed union of an organic azide and a terminal alkyne to create a 1,4-disubstituted 1,2,3-triazole (Figure A). A wide variety of options exist for the catalyst, ranging from commercially available saltse.g., the Sharpless–Folkin catalyst (CuSO 4 ·5H 2 O reduced by sodium ascorbate) , to Cu­(I) complexes stabilized by ancillary ligands. , Interestingly, silver-, ruthenium-, iridium-, and nickel-catalyzed azide–alkyne cycloadditions have also been reported, but the copper-mediated flavor remains the gold standard (no pun intended!). CuAAC reactions are simple, rapid, and tolerant of oxygen and water .…”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
See 3 more Smart Citations
“…As its name suggests, the CuAAC reaction is predicated on the Cu­(I)-catalyzed union of an organic azide and a terminal alkyne to create a 1,4-disubstituted 1,2,3-triazole (Figure A). A wide variety of options exist for the catalyst, ranging from commercially available saltse.g., the Sharpless–Folkin catalyst (CuSO 4 ·5H 2 O reduced by sodium ascorbate) , to Cu­(I) complexes stabilized by ancillary ligands. , Interestingly, silver-, ruthenium-, iridium-, and nickel-catalyzed azide–alkyne cycloadditions have also been reported, but the copper-mediated flavor remains the gold standard (no pun intended!). CuAAC reactions are simple, rapid, and tolerant of oxygen and water .…”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
“…In these scenarios, the CuAAC ligation can be particularly useful, as azide- or alkyne-bearing prosthetic groups can be radiolabeled and then clicked to vectors in a one-pot two-step schema. This approach is especially popular in the synthesis of 18 F-labeled agents, as evidenced by a large library of 18 F-labeled clickable groups that includes [ 18 F]­fluorobenzyl azides, , azide- and alkyne-modified [ 18 F]­fluoropyridines, [ 18 F]­fluoroalkyl azides, , [ 18 F]­fluorocarbohydrate azides, ,, [ 18 F]­fluoropolyoxyethylene azides, ,, 3-[ 18 F]­fluoropropyne, 5-[ 18 F]­fluoropentyne, , ethynyl-4-[ 18 F]­fluorobenzene, and [ 18 F]­AMBF 3 . , In one recent example, Wang et al reported the synthesis of a modular scaffold for combined near-infrared (NIR) fluorescence and PET imaging via the CuAAC-mediated modification of an azide-bearing NIR dye with an 18 F-labeled alkyne . The work of Walker et al provides a particularly fine example of the pros and cons of a two-step, CuAAC-driven approach to radiofluorination (Figure ).…”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 18 F]-PC44:12 (2). Due to our extensive experience with [ 18 F]-fluoroethyl azide click chemistry as well as the compatibility of this strategy with a large number of functional groups, we chose a click chemistry approach to radiolabel the PC44:12 phospholipid at the N-methyl position [18,19]. To demonstrate its possible use as a radiotracer for prostate cancer, initial biodistribution and tumor uptake in LNCaP tumor-bearing mice was evaluated and compared to [ 18 F]-fluoromethylcholine via dynamic PET imaging.…”
Section: Introductionmentioning
confidence: 99%